International corporate planning - Brooke, Michael Z.; Beusekom, Mark van. (London ; Marshfield, Mass. : Pitman, 1979)
This book legitimizes on international planning
Includes bibliographical references and index.
mf 23/01/2019
Loans
Keywords: Business planning; International business enterprises